Pengkayaan Sumberdaya Ikan di Oxbow Melalui Penerapan Artifisial Habitat Oleh Nelayan Desa Rantau Baru Kecamatan Pangkalan Kerinci Kabupaten Pelalawan Riau - Ridwan Manda Putra; Sukendi Sukendi; Dewita Dewita; Budijono Budijono; Syahril Nedi (CANANG: Jurnal Pengabdian Masyarakat, 2023)
This community dedication is aimed at informing the community about the creation of a new fish habitat by floating a set of artificial habitat units in the selected zone based on oxbow batimetry, so that the fish resources in the oxbows remain available. The dedication activities were carried out in the Rantau Baru Village, Pangkalan Kerinci  district of Pelalawan Regency, and the delivery of material was carried out on August 2, 2023. There are 30 participants in this selection, consisting of the village equipment and the oxbow fishermen in the New Rantau Village. The materials to be provided for this dedication are: (a) Oxbow and its uses; (b) biodiversity of fish and public waters; (c) threats to fish biodiversity; (d) artificial habitat; and (e) methods of creation, operation, and maintenance of artificial habitat. The method used in the implementation of this activity is to survey the field first, then conduct deliberations in the form of lectures and interactive discussions, followed by demonstrating the artificial creation of habitats and placing the tools in the oxbow. The results of the evaluation of the change in knowledge carried out on 30 participants in the service to the community showed that 5 people (16.7%) have been able to absorb the material given with the preaching very well, 13 people (43.3%) can absorb materials given with good preaching, 10 people (33.3%) can absorb material with sufficient preaching, and 2 people (6.7%) could absorb material with less preaching. As for the impact on implementation in the field, there has been a process of dissemination of knowledge to fishermen carried out by community leaders. So that the diversity of fish in public waters (especially the oxbow lake) that exists in the Rantau Baru Village can be well awakened.